Fault lines : a primer on race, science and society - Jansen, Jonathan D.; Walters, Cyrill (African Sun Media, 2020)
"What is the link, if any, between race and disease? How did the term baster as 'mixed race'come to be mistranslated from 'incest'in the Hebrew Bible? What are the roots of racial thinking in South African universities? How does music fall on the ear of black and white listeners? Are new developments in genetics simply a backdoor for the return of eugenics? For the first time, leading scholars in South Africa from different disciplines take on some of these difficult questions about race, science and society in the aftermath of apartheid. This book offers an important foundation for students pursuing a broader education than what a typical degree provides, and a must-read resource for every citizen concerned about the lingering effects of race and racism in South Africa and other parts of the world."--Publisher's description